HUBUNGAN RIWAYAT PAPARAN PESTISIDA IBU SAAT HAMIL DENGAN KEJADIAN STUNTING ANAK USIA 2- 5 TAHUN (Studi Kasus di Wilayah Kerja Puskesmas Sawangan 1, Kabupaten Magelang) - Annisa Aulia Nurrohmah; Nurjazuli Nurjazuli; Tri Joko (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Background: Stunting is identified by Z score index body-length-for-age. Z score index body-length-for-age children with stunting is lower than -2SD. Children with stunting have a risk of decreasing learning achievement, productivity and degenerative diseases in the future. Chemicals in the environment (xenobiotics) such as pesticides might cause stunting.Methods: It was an observational analytic research with case-control study design. The population in this study were mothers who had children aged 2-5 years in the Puskesmas Sawangan 1 work area. Samples were grouped into cases and controls with 51 subjects in each group. Primary data was obtained through interviews. Data were analyzed by univariate and bivariate using contingency coefficients.Results: Mixing pesticides (p = 0,022), washing spraying equipment (p = 0,021), spraying (p = 0,021) and completeness of PPE (p = 0,041) are associated with the incidence of stunting in children aged 2-5 years. While the duration of work (p = 0.061) and the presence of pesticides in the house (p = 0.208) does not associated with the incidence of stunting of children aged 2-5 years.